2009
DOI: 10.1016/j.fertnstert.2008.04.060
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of ovarian function in girls and women with classic galactosemia

Abstract: Study objective-To determine whether premature ovarian insufficiency (POI) associated with classic galactosemia results from a true deficiency of ovarian function or from aberrant follicle stimulating hormone (FSH). Design-Cross-sectional study Setting-University research laboratoryPatients or other participants-Study subjects included 35 girls and women with galactosemia and 43 control girls and women between the ages of <1 yrs to 51 yrs.Interventions-Blood sampling and medical and reproductive histories were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 39 publications
3
57
0
1
Order By: Relevance
“…The authors contrast their case with results published by our group from a study of 35 galactosemic girls and women (2). We demonstrated that 32 of 35 of these individuals had low to undetectable AMH, and noted the similarity of this frequency with rates of clinical ovarian insufficiency reported for this patient population.…”
supporting
confidence: 38%
“…The authors contrast their case with results published by our group from a study of 35 galactosemic girls and women (2). We demonstrated that 32 of 35 of these individuals had low to undetectable AMH, and noted the similarity of this frequency with rates of clinical ovarian insufficiency reported for this patient population.…”
supporting
confidence: 38%
“…Over 80% of galactosaemia females suffer from POI (91% in Irish female patients) (Waggoner et al 1990;Sanders et al 2009;Coss et al 2013). The clinical presentation varies from primary amenorrhea to delayed pubertal development followed by irregular menses or secondary amenorrhea.…”
Section: Congenital Disorders Of Glycosylationmentioning
confidence: 99%
“…Classic galactosemia is predicted in the newborn to occur in cases of absent or barely detectable GALT enzyme activity, persistent elevations of galactose-1-phosphate (erythrocyte range above 20 mg% in the newborn with peak >120 mg% and persisting with diet between 1 and 5 mg%) and galactitol (urine excretion range above 1000 μmol/mmol of creatinine in the newborn with peak greater than 50,000 μmol/mmol of creatinine and persisting with diet between 100 and 400 μmol/mmol of creatinine), and evidence of or the propensity for a neonatal life-threatening multiorgan disorder particularly with liver failure and the risk of lethal E. coli sepsis. Additional defining features include markedly diminished oxidation of [1-13 C] galactose to 13 CO 2 in a 2-5 h breath test (Berry et al 1995a(Berry et al , 1997Barbouth et al 2007), elevated serum FSH and decreased anti-Müllerian hormone (AMH) levels in female infants and children (Sanders et al 2009), and brain MRI lesions (white matter hyperintensities, cortical atrophy and cerebellar atrophy). Most of these patients will possess severe GALT gene mutations such as Q188R, K285N, Δ5.2 kb deletion and L195P either in homozygous or compound heterozygous states.…”
mentioning
confidence: 99%